The Engagement of the Pelvic Floor Muscles to the Urethra, Does Variation in Point of Action Exist? - van Geen, Frank-Jan; de Jong, Henriëtte M. Y.; de Jong, Tom P. V. M.; de Mooij, Keetje L. (Frontiers in Pediatrics, 2020)
Purpose: Lower urinary tract dysfunction (LUTD) occurs frequently in girls and may display a spinning top urethra (STU) on voiding cysto-urethrogram (VCUG) in case of dysfunctional voiding. A STU presents as a narrowing of the urethra caused by a lack of relaxation of the pelvic floor musculature during micturition and may vary in length between the proximal and the distal urethra. Although a STU has been recognised since 1960 as a pathological entity on VCUG, no reports exist on the different levels of engagement of the pelvic floor muscles to the urethra as expressed by the varying length of the phenomenon. The aim of our study is to demonstrate the wide anatomical variation in the level of engagement of the pelvic floor musculature to the urethra. Material and Methods: Dynamic ultrasound videos of pelvic floor musculature of 40 girls with LUTD were reassessed by three observers, looking for the level of engagement of the puborectalis muscle (PRM) to the urethra during coughing, Valsalva and hold-up manoeuvre. Three levels were defined, for the level of engagement of the pelvic floor to the urethra, proximal, mid and distal. Intra- and inter-rater variability was analysed using Cohen’s kappa statistics. Results: A wide range of points of action was found on the assessed ultrasound videos. Intra- and inter-rater agreement showed different levels of conformity, varying over a wide spectrum (intra-rater kappa 0.145 – 0.546; inter-rater kappa -0.1030.724). Throughout the assessed videos, all not-corresponding intra-rater observations differed maximally one category. Of the not-corresponding inter-rater observations, 90% differed maximally one category. Conclusion: A wide anatomical variation in levels of engagement of the PRM to the urethra does exist. The clinical value of this finding, whether the point of engagement influences symptomatology or treatment success of LUTD, is currently being studied.